Prediktor Faktor Menstruasi dan Asupan Fe terhadap Peningkatan Kejadian Anemia pada Remaja Putri - Riyanto, Riyanto; Lestari, Gangsar Indah; Dayani, Tiara Rica; Herbawani, Chahya Kharin (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2023)
Introduction: Anaemia in adolescent girls is a major public health problem. Menstruation is the main cause. Fe tablet programmes have been introduced, but the incidence of anaemia is still high. Purpose: This study was to determine the prevalence of anemia and estimate the relationship between major menstrual factors and other covariate variables: BMI, knowledge, tea drinking patterns and Fe tablet intake with the incidence of anemia in adolescent girls. Methods: A cross sectional study was conducted on 69 adolescent girls from 3 schools in an Islamic boarding school in the Metro city area to analyse menstrual patterns by involving other confounding variables. Questionnaires were used to measure menstrual pattern, knowledge level, iron intake, and drinking the after meal. Anthropometry of respondents was measured to determine their BMI and nutrition and haemoblobin was checked using Hb Digital (easy touch) to determine anaemia status. Data analysis used multivariate analysis with multiple logistic regression test estimation model with a significance level (α) of 0.05. Results: We found the incidence of anaemia in adolescents was 68.1%. The results of bivariate analysis showed there was a significant association of the incidence of anaemia among adolescent girls with menstrual pattern disorder (p-value 0.001; OR 6.250 CI 95% 2.057-18.987), nutritional status (BMI) with p-value 0.032 (OR 3.960; CI 95% 1.163-13.488), knowledge (p-value 0.050; OR 3.083 CI 95%: 1.035-9.188), while the tea drinking factor showed no association. Multivariate analysis obtained a large factor of menstrual pattern disorder with ORadjusted 6.679) and lack of Fe tablet intake with ORadjusted 3.025. Conclusion: The incidence of anaemia in adolescent girls is at risk of increasing six times, when experiencing abnormal menstrual patterns. Fe intake, lack of knowledge and poor nutritional status are other triggering factors for adolescent girls to experience anaemia. It is importance to reduce and prevent anaemia in adolescents by eliminating these factors. Latar Belakang: Anemia pada remaja putri merupakan masalah kesehatan masyarakat utama. Menstruasi menjadi penyebab utamanya. Program pemberian tablet Fe sudah diberikan, Namun kejadian anemia masih tinggi. Tujuan: Studi ini untuk mengetahui prevalensi anemia dan mengestimasi hubungan faktor utama menstruasi dan variabel kovariat lain: IMT, pengetahuan, pola minum teh dan asupan tablet Fe dengan kejadian anemia pada remaja putri. Metode: Studi cross sectional study dilakukan pada 69 remaja putri dari 3 sekolah di pondok pesantren islam di wilayah kota Metro untuk menganalisis pola menstruasi dengan melibatkan variabel confounding lainnya. Kuesioner digunakan untuk mengukur pola menstruasi, tingkat pengetahuan, asupan zat besi, dan minum the setelah makan. Antropometri responden diukur menentukan dan gizi (IMT) mereka dan haemoblobin diperiksa menggunakan alat Hb Digital (easy touch) untuk menentukan status anemia. Analisis data digunakan analisis multivariat dengan uji multiple regresi logistik model estimasi dengan tingkat kemaknaan (α) 0,05. Hasil: Kami menemukan kejadian anemia pada remaja berjumlah 68,1%. Hasil analisis bivariat menunjukkan ada hubungan signifikan kejadian kejadian anemia remaja putri dengan gangguan pola menstruasi (p-value 0,001; OR 6,250 CI 95% 2,057-18,987), status gizi (IMT) dengan p-value 0,032 (OR 3,960; CI 95% 1,163-13,488), pengetahuan (p-value 0,050; OR 3,083 CI 95%: 1,035-9,188), sedangkan faktor minum teh tidak menunjukkan ada hubungan. Analisis multivariat diperoleh hasil besar faktor gangguan pola menstruasi dengan ORadjusted 6,679) dan kurang asupan tablet Fe dengan ORadjusted 3,025. Simpulan: Kejadian anemia remaja putri berisiko meningkat enam kali, bila mengalami pola menstruasi yang tidak normal. Asupan zat fe, pengetahuan kurang dan status gizi tidak baik menjadi faktor pemicu lain remaja putri mengalami anemia. Pentingnya upaya menurunkan dan encegah anemia pada remaja dengan mengelinasi faktor-faktor tersebut.